PEMANFAATAN MATERIAL LIMBAH PADA CAMPURAN BETON ASPAL CAMPURAN PANAS - Mashuri, Mashuri; Batti, Joy Fredy (MEKTEK, 2011)
This paper describes the utilization of waste materials such as Styrofoam, Plastic PVC, coal ash dust and tiremarks on the hot mix asphalt concrete mixtures. The purpose of this paper is to explain that the potential useof waste materials in hot mix asphalt pavement.The data presented in this study is a secondary data from the research at the Laboratory of Transportationand Highways Faculty of Engineering, University of Tadulako that has been done by writers and members ofother researchers. In this paper the variables considered are the stability and durability of asphalt concretemixtures using the waste material.The results of this paper presentation shows the potential for material Styrofoam, plastic pvc, dust and coalash can be used in hot mix asphalt concrete mixtures